Simulation of the transfer and fate of γ-HCH in epikarst system. (April 2016) - Sun, Yuchuan; Liang, Zuobing; Xiang, Xinyi; Lan, Jiacheng; Zhang, Qiang; Yuan, Daoxian
Abstract: The thin surface soil layer and karst features in karst terrains lead to poor filtration, poor pre-purification and rapid infiltration, so that karst groundwater systems are particularly vulnerable to contamination. Due to its extensive use in past, gamma-hexachlorocyclohexane (γ-HCH) is ubiquitous in various environmental compartments of China, even though it has been prohibited since 1984. However, very little is known about its movement and behavior in special karst system. In this study, a dynamic fugacity model was established for γ-HCH in epikarst system via dividing the karst soil into multiple layers coupled with the physical–chemical properties of γ-HCH. The simulated results in soil profile were in good agreement with the measured values of γ-HCH. The modeled results predict that only 18 g γ-HCH will be left in the studied area in 2020, which is only 0.4% of the largest reserves in 1983, and about 99.99% of γ-HCH will remains in soil. The concentrations of γ-HCH in air, plant and 0–20 cm layer soil in the studied area descended quickly after HCHs was prohibited in 1984, while its concentration in soil layer deeper than 20 cm (deeper soil) increased continuously till 1997. The dominant transfer process of γ-HCH between the adjacent compartments in the studied area was from 0−20 cm layer to the deeper soil. Sensitivity analysis results showed that emission rate, infiltration coefficient, total organic carbon of soil, degradation rate in soil, compartment area and volume were the top six influential parameters for predicting γ-HCH concentration. Highlights: A dynamic fugacity model was established for the transfer and fate of γ-HCH in epikarst system. The modeling results in soil profile are in good agreement with the measured values of γ-HCH. The dominant process of γ-HCH in epikarst system was the transfer from 0 to 20 cm layer to deeper soil.